Forgetting to Remember or Remembering to Forget - A Study of the Recall Period Length in Health Care Survey Questions - Gustav Kjellsson; Philip Clarke; Ulf-G. Gerdtham (Lund University, School of Economics and Management, Department of Economics, 2013)
Self-reported data on utilization of health care is a key input into a range of studies. However, the length of the recall period in self-reported health care questions varies between surveys and this variation may affect the results of the studies. While longer recall periods include more information, shorter recall periods generally imply smaller bias. This article examines the role of the recall period length for the quality of self-reported data by comparing registered hospitalization with self-reported hospitalizations of respondents that are exposed to a varying recall period length of one, three, six, or twelve month. Our findings have conflicting implications for survey design as the preferred length of recall period depends on the objective of analysis. If the objective is an aggregated measure of hospitalization, longer recall periods are preferred whereas shorter recall periods may be considered for a more micro-oriented level analysis since the association between individual characteristics (e.g. education) and recall error increases with the length of the recall period.
Keywords: C42; C83; I10; 330; Survey Methods; Health survey; Hospitalization; Recall error; Recall periods